New Insights Into the Persistent Effects of Acute Exposure to AFB1 on Rat Liver - Yan, Jiahui; Chen, Lin; Zhang, Li; Zhang, Zhaohuan; Zhao, Yong; Wang, Yuan; Ou, Jie (Frontiers in Microbiology, 2022)
Aflatoxin B1 (AFB1) has mutagenesis, carcinogenesis and teratogenesis effects and mainly found in food crops and their processed foods. AFB1 exposure can cause acute or chronic liver poisoning, but there are few studies on the persistent effects of acute AFB1 exposure on the liver. In this study, rat liver injury models were established 2 and 7 days after single exposure to high and low doses of AFB1. The persistent effects of AFB1 single acute exposure (ASAE) on rat liver were analyzed from the phenotypic and genetic levels. The results showed that compared with the control group, liver function indexes, MDA content in liver and the number of apoptotic hepatocytes in model groups increased to the highest on 2nd days after ASAE. However, the changes of liver coefficient were most significant on the 7th day after ASAE. The results of liver pathology showed that the liver injury was not alleviated and the activities of antioxidant enzymes GSH-Px and SOD were the lowest on the 7th day. RNA-Seq results indicated that there were 236, 33, 679, and 78 significantly differentially expressed genes (DEGs) in the model groups (LA-2d, LA-7d, HA-2d, HA-7d) compared with the control group. Among them, the Gtse1 genes related to the proliferation, differentiation and metastasis of liver cancer cells, the Lama5 and Fabp4 gene related to the inflammatory response were significantly DEGs in the four model groups, and the differential expression of the immune system-related Bcl6 gene increased with the prolonged observation time after ASAE. In conclusion, ASAE can cause persistent liver damage in rats. The persistently affected genes Lama5, Gtse1, Fabp4, and Bcl6 possess the potential to be therapeutic targets for liver disease induced by AFB1.